Caracterização in vitro de técnica biomagnética empregando magnetômetros 3D para avaliar tempo de trânsito esofagiano - Quini, Caio César [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The biomagnetic techniques use different magnetic field detectors to measure parameters of the human physiology. Those techniques present the advantage of being noninvasive and radiation free. Among them we can show up the Superconducting Quantum Interference Device (SQUID), the Current Alternate Biosusceptometry (ACB) and, more recently, the employment of anisotropic magnetoresistive sensors. Those magnetic sensors have a low cost and good sensitivity to measure different physiological parameters using magnetic markers. The biomagnetic techniques have being used successfully through study on the characteristics of the gastrointestinal tract. Recent research, the magnetoresistors were used to evaluate the transit time and localization of magnetic sources in different parts of the gastrointestinal tract. The objective of this work is the characterization, with in vitro tests, of a biomagnetic instrumentation using two 3-axis magnetoresistors arranged in a gradiometric coplanar setup to evaluate esophageal transit time, analyze and compare the results of experimental signals and the magnetic theory, as well as evaluate the instrumentation gain with use of tri-axial sensor front to the mono-axial sensor. The instrumentation is composed by two three-axis sensing magnetometers, precision power supply and amplifier electronic circuits. The sensors fixed in a coplanar setup were separate by distance of 18 cm. The sensitivity tests had been carried through using a cylindrical magnet (ø = 4 mm and h = 4 mm) of neodymium-iron-boron (grid 35). The tests were done moving the permanent magnet on the sensors parallel axis, simulating the food transit in... (Complete abstract click electronic access below)

As técnicas biomagnéticas utilizam diferentes detectores de campo magnético para medir parâmetros da fisiologia humana. Essas técnicas apresentam a vantagem de não ser invasiva e ser livre de radiação ionizante. Dentre elas podemos destacar o Superconducting Quantum Interference Device (SQUID), a biossusceptometria de corrente alternada e, mais recentemente, o emprego de sensores do tipo magnetorresistor anisotrópico. Os magnetorresistores apresentam a vantagem de serem de baixo custo e possuir boa sensibilidade para medir diferentes parâmetros fisiológicos utilizando marcadores magnéticos. Devido às características do trato gastrintestinal, as técnicas biomagnéticas vêm sendo empregadas com bastante sucesso em seu estudo. Em recente pesquisa, os magnetorresistores foram empregados para avaliar o tempo de trânsito e localização de fontes magnéticas em diferentes partes do trato gastrintestinal. O objetivo deste trabalho é caracterizar com testes in vitro uma instrumentação biomagnética composta por dois magnetorresistores tri-axiais (3D) arranjados de forma gradiométrica coplanar para avaliar tempo de trânsito esofagiano, processar os sinais e comparar os resultados experimentais com a teoria magnética, bem como avaliar o ganho da instrumentação com uso de sensor tri-axial frente ao sensor mono-axial. A instrumentação é formada por dois magnetômetros com três eixos de detecção conectados a circuitos eletrônicos de alimentação e amplificação. Os sensores foram fixados de forma coplanar separados com 18 cm de distância. Os testes de sensibilidade foram realizados usando um magneto cilíndrico (ø = 4 mm e h = 4 mm) de... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Esofago - Biomagnetismo; Esofago; Magnetômetros 3D; Esophageal transit